PREDICTING ATTENDANCE OF A PREVENTIVE PARENTING INTERVENTION FOR VERY PRETERM INFANTS. Issue 6 (19th October 2018) - Winter, Leanne; Sanders, Matthew R.; N Boyd, Roslyn; Pritchard, Margo; Gray, Peter H.; Whittingham, Koa; Forrest, Kylee; Webb, Lachlan; Marquart, Louise; Colditz, Paul B
ABSTRACT: Preventive parenting interventions can experience challenges in maximizing dosage, or the amount of intervention received by parents. This study examined the associations of baseline mother, father, and very preterm infant (VPT; <32 weeks) characteristics with satisfactory intervention attendance of the family within a randomized controlled trial of Baby Triple P for Preterm Infants (Colditz et al., 2015). Mothers ( n = 160) and fathers ( n = 115) completed questionnaires prior to the randomization of family units ( n = 160) to receive the intervention. Satisfactory session attendance (seven or eight sessions of eight in total) was achieved by 114 families (71.25%). In the logistic model for mothers, satisfactory attendance of the family was more likely when infants were extremely low birth weight (ELBW), odds ratio (OR) = 2.81, 95% confidence interval (CI) [1.16, 6.80], when the mother had a university, OR = 11.38, 95% CI [4.03, 32.19], or trade‐certificate‐level education, OR = 4.97, 95% CI [1.93, 12.84], or when she was not under financial stress, OR = 3.53, 95% CI [1.34, 9.28]. A similar pattern of results was found in the model for fathers. Session attendance of preventive parenting interventions for VPT infants may be improved by increasing the engagement of parents with infants not born ELBW, who have lower education, or are experiencing financial stress.